(3GdJShjb GdOhGFj s - (3cGaj(B, (3eUWai jhSas ((3YeGfs (3OGQ GdGHJcGQ ddfTQ hGdJhRjYs, 2022)
(3jbOe cJGH (B"(3GdJShjb GdOhGFj(B" (3fXQI TGedI Ydi YGde GdJShjb aj GdUfGYI GdOhGFjI(B. (3jHOC GdcJGH HJSdjW GdVhA Ydi WHjYI GdUfGYGJ GdOhGFjI hJMOjGJgG GdaQjOI(B. (3Ke jfJbd Edi JbOje NdajI YGeI Yf eHGOF GdJShjb hHjFI GdYed GdJShjbjI HTcd YGe, eY GdJQcjR Ydi GdYhGed GdJj JDKQ Ydi bQGQGJ GdTQGA aj eLGd GdCOhjI(B. (3jJfGhd GdaUd GdKGdK OQGSI GdCShGb GdOhGFjI GdeNJdaI hOhGaY GdeSJgdcjf YfO TQGA GdCOhjI, eY GdJQcjR Ydi GdYhGed GdfaSjI hGdGLJeGYjI GdJj JDKQ Ydi Sdhcge(B. (3hCNjkQG, jHMK GdaUd GdQGHY aj GdbQGQGJ GdGSJQGJjLjI GdeJYdbI HGdefJLGJ GdOhGFjI, eKd JMOjO GdejRGJ GdJfGaSjI ddefJL, hJSYjQg, hJhRjYg(B. (3jYJHQ gPG GdcJGH eQLkYG bjkeG ddeNJUjf aj eLGd GdJShjb GdOhGFj, MjK jhaQ dge agkeG YejkbG ddJMOjGJ hGdaQU GdJj JhGLg gPG GdbWGY(B.s
Keywords: (3GdJShjb GdOhGFjs; (3GdJShjb(B- (3GdCOhjI s